Pengaruh Chat GPT Terhadap Kemampuan Menganalisis Data pada Mahasiswa - Taufik Hidayat; M Nibras Ramzi; M Arya Akbar; Wahyu Hidayat; Dina Indriana (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the impact of Chat GPT usage on data analysis skills among students. The research employs a quantitative approach with data collection through questionnaires distributed to 100 respondents. The data analysis technique used is simple linear regression to measure the relationship between the independent variable (Chat GPT usage) and the dependent variable (data analysis skills). The analysis results show a significant negative relationship between Chat GPT usage and students' data analysis skills, with the regression equation Y = 16.382 - 0.213X. The regression coefficient of -0.213 indicates that for every one-unit increase in Chat GPT usage, students' data analysis skills are expected to decrease by 0.213 units, with a significance level of 0.001 at a 99% confidence level. The constant value of 16.382 indicates that data analysis skills are at this level when Chat GPT usage is zero. These findings underscore the importance of wise management in the use of Chat GPT within academic environments. While this technology has the potential to support the learning process, its unstructured use could negatively affect the development of students' analytical skills. Therefore, policies and guidelines for AI usage in education need to be designed to maximize benefits and minimize emerging risks.